2019
DOI: 10.3348/kjr.2018.0515
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on the Value of Ultrasound Microflow Assessment to Distinguish Malignant from Benign Solid Breast Masses: Association between Ultrasound Parameters and Histologic Microvessel Densities

Abstract: Objective To investigate the value of ultrasound (US) microflow assessment in distinguishing malignant from benign solid breast masses as well as the association between US parameters and histologic microvessel density (MVD). Materials and Methods Ninety-eight breast masses (57 benign and 41 malignant) were examined using Superb Microvascular Imaging (SMI) and contrast-enhanced US (CEUS) before biopsy. Two radiologists evaluated the quantitative and qualitative vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(134 citation statements)
references
References 34 publications
8
123
0
3
Order By: Relevance
“…The optimal cutoff values of the SMIVI varied from 4.0% to 8.9% for differentiating benign and malignant breast masses (25,26). In both studies, an SMI image with the most abundant Doppler signal was retrospectively selected among the previously obtained images and drew the ROI for SMIVI using the postprocessing software masses (25,26). In our study, each observer selected Doppler images and drew the ROI for kjronline.org were less than 10 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal cutoff values of the SMIVI varied from 4.0% to 8.9% for differentiating benign and malignant breast masses (25,26). In both studies, an SMI image with the most abundant Doppler signal was retrospectively selected among the previously obtained images and drew the ROI for SMIVI using the postprocessing software masses (25,26). In our study, each observer selected Doppler images and drew the ROI for kjronline.org were less than 10 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…SMI VI is the percentage ratio between the pixels for the Doppler signal and those for the total lesion ( 23 24 ). Studies investigating the diagnostic value of SMI VI in differentiating benign and malignant breast masses are relatively few ( 25 26 ). However, studies assessing the cutoff values of the quantitative parameters derived from both SWE and SMI and the diagnostic performance of combining these quantitative parameters and B-mode US-based breast imaging reporting and data system (BI-RADS) have not been conducted yet.…”
Section: Introductionmentioning
confidence: 99%
“…Of that benign masses tend to display the non-vascular pattern, a linear or curvilinear pattern and a treelike pattern, while malignant masses tend to display the root hair-like pattern and the crab claw-like pattern [12]. Smart 3-D SMI can quantitatively assess tumor vascularity via measuring vascularity index (VI) on 2-D SMI images obtained with the qualitative guidance of 3-D SMI images, which is significantly higher in malignant lesions than that in benign ones and may potentially serve as a noninvasive tool to accurately characterize benign versus malignant breast lesions [20]. Present studies have revealed that SMI is more accurate in the detection and characterization of breast lesions comparable with mammography X-ray and conventional CDFI scanning [15].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the titles and abstracts of all articles and excluded 21 articles; full texts and data integrity were also reviewed and 11 were further excluded. Finally, 15 studies that met all inclusion criteria were included in this meta-analysis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Figure 1 showed the selection process of eligible articles.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Compared with BI-RADS, the VI offers improved diagnostic efficiency. Park et al 22 studied the diagnostic efficacy of degradation of BI-RADS 4A lesions with 8.9 as the cutoff value of VI. Twenty-six lesions were downgraded to BI-RADS 3 with improved PPV (56.9% vs 41.8%) and AUC (0.728 vs 0.500, p < 0.001) compared to the original BI-RADS assessment, consistent with our results.…”
Section: Discussionmentioning
confidence: 99%